The Influence of Social Media on Marketing Communication Student - Widiyanto, Widiyanto; Seneru, Wistina; Iin Avitasari; Arwening, Komang Yumi; Wati, Nesa (LPPM STIAB JINARAKKHITA LAMPUNG, 2024)
This study aims to determine the influence of social media use on the students marketing communication strategy at the Buddhist Communication Science Department, Jinarakkhita Buddhist College of Lampung, Indonesia. The problems that occur to students are the lack of understanding of the platform, features, and how social media supports the delivery of marketing messages, the gap between the potential of social media and its use in the context of marketing, the lack of digital literacy skills and an understanding of marketing communication strategies that are sufficient to utilize social media optimally. The research with a quantitative approach, data was collected through a survey to students of Buddhist Communication Science Department, with a population of 52 students. This research was conducted at the Jinarakkhita Buddhist College of Lampung, Indonesia. The research instrument in the form of a questionnaire was analyzed using SPSS version 26 for validity, reliability, and linear regression tests. The results showed that the intensity of social media use had a significant relationship with the effectiveness of marketing communication strategies, with a determination coefficient of 27.4%. These findings contribute to the development of digital marketing communication theory and provide recommendations for universities to improve students' digital literacy to support their marketing communication skills.